1991
DOI: 10.1111/j.1600-0447.1991.tb03136.x
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine and imipramine treatment of depressive patients in a controlled multicentre study with plasma amino acid measurements

Abstract: In a 12-week double-blind study with 36 patients with major depressive episode (DSM-III), paroxetine (Seroxat, Aropax) showed significantly quicker onset of efficacy on the Melancholia Scale, and better tolerance than imipramine. Plasma concentration analyses showed no clear concentration-efficacy correlation in either treatment group. During long-term treatment paroxetine seemed to be superior to imipramine in preventing relapse; both treatments were well tolerated. A significant correlation between baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…For instance, Moller et al (1986Moller et al ( , 1990 and Lucca et al (1994) found that lower Trp:LNAA ratios predicted a better response to serontonergic antidepressants. However, the results from other studies have not been completely consistent (Moller et al 1990 ;Nielsen et al 1991;Moller, 1993). In an earlier study of ours (Porter et al 2003), and in this study (Porter et al in press) we have not found that a higher Trp:LNAA ratio predicted a poorer response to antidepressants in general or to serotonergic antidepressants.…”
Section: Discussioncontrasting
confidence: 64%
“…For instance, Moller et al (1986Moller et al ( , 1990 and Lucca et al (1994) found that lower Trp:LNAA ratios predicted a better response to serontonergic antidepressants. However, the results from other studies have not been completely consistent (Moller et al 1990 ;Nielsen et al 1991;Moller, 1993). In an earlier study of ours (Porter et al 2003), and in this study (Porter et al in press) we have not found that a higher Trp:LNAA ratio predicted a poorer response to antidepressants in general or to serotonergic antidepressants.…”
Section: Discussioncontrasting
confidence: 64%
“…Plasma TRP levels have also been shown to predict response to SSRIs. Thus, Lucini et al (1996) suggest that the TRP/LNAA ratio could be of predictive value to antidepressant response, and Nielsen et al (1991) reported a significant correlation between baseline plasma TRP/LNAA ratio and the severity of depression after paroxetine treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Eight studies were excluded as they did not specify status or included both in-and out-patients. Exceptions to these exclusion criteria were a predominantly in-patient study with only four out-patients (Nielsen et al, 1991) and one which started with in-patients who were subsequently discharged (Lund Laursen et al, 1985); these were both taken to be in-patient studies. We addressed the issue of severity by analysing more and less severe patient groups by taking a median split of severity on the initial HDRS (using the mean of the scores of the two treatment groups for each study) stratified according to use of the 17-and 21-item HDRS (respective medians 24.45 and 26.04).…”
Section: Subgroup Analysismentioning
confidence: 99%